Biallelic variants in the conserved ribosomal protein chaperone gene PDCD2 are associated with hydrops fetalis and early pregnancy loss - Anne-Marie Landry-Voyer; Tess Holling; Emily K. Mis; Zabih Mir Hassani; Malik Alawi; Weizhen Ji; Lauren Jeffries; Kerstin Kutsche; François Bachand; Saquib A. Lakhani (Proceedings of the National Academy of Sciences, 2025)
Pregnancy loss is a major problem in clinical medicine with devastating consequences for families. Next generation sequencing has improved our ability to identify underlying molecular causes, though over half of all cases lack a clear etiology. Here, we began with clinical evaluation combined with exome sequencing across independent families to identify bi-allelic candidate genetic variants in the Programmed Cell Death 2 (PDCD2) gene in multiple fetuses with nonimmune hydrops fetalis (NIHF). PDCD2 is an evolutionarily conserved protein with no prior association with monogenic disorders. PDCD2 is known to act as a molecular chaperone for the ribosomal protein uS5, and this complex formation is important for incorporation of uS5 into the 40S subunit, a crucial step in ribosome biogenesis. Primary fibroblasts from an affected fetus and cell lines expressing PDCD2 patient variants demonstrated reduced levels of PDCD2, reduced PDCD2 binding to uS5, and altered ribosomal RNA processing. Xenopus tadpoles with Pdcd2 knockdown demonstrated developmental defects and edema, reminiscent of the NIHF seen in affected fetuses, and showed altered ribosomal RNA processing. Through genetic, biochemical, and in vivo approaches, we provide evidence that bi-allelic PDCD2 variants cause an autosomal recessive ribosomal biogenesis disorder resulting in pregnancy loss.